2017
DOI: 10.3389/fimmu.2017.01648
|View full text |Cite
|
Sign up to set email alerts
|

F-Type Lectins: A Highly Diversified Family of Fucose-Binding Proteins with a Unique Sequence Motif and Structural Fold, Involved in Self/Non-Self-Recognition

Abstract: The F-type lectin (FTL) family is one of the most recent to be identified and structurally characterized. Members of the FTL family are characterized by a fucose recognition domain [F-type lectin domain (FTLD)] that displays a novel jellyroll fold (“F-type” fold) and unique carbohydrate- and calcium-binding sequence motifs. This novel lectin family comprises widely distributed proteins exhibiting single, double, or greater multiples of the FTLD, either tandemly arrayed or combined with other structurally and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…F-type lectins are fucose-binding lectins with L-fucose (HX(26) RXDX(4)R/K) and calcium-binding sequence motifs and an F-type lectin fold (Bianchet et al 2002). They are phylogenetically widespread but selectively distributed in viruses, bacteria and eukaryotes (Bishnoi et al 2015), and have diverse functions ranging from innate immunity in fishes and amphibians to protoplast regeneration in the green alga, Bryopsis plumosa and virulence in the bacteria, Streptococcus pneumoniae and Streptococcus mitis (Vasta et al 2017). Several eukaryotic F-type lectins (e.g., Anguilla anguilla agglutinin (AAA), Morone saxatilis agglutinin (MSA)) (Bianchet et al 2002(Bianchet et al , 2010 and the F-type lectin domains (FLDs) of a couple of bacterial proteins (Streptococcus pneumoniae SP2159 and Streptococcus mitis lectinolysin) (Boraston et al 2006;Farrand et al 2008;Feil et al 2012) have been biochemically and structurally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…F-type lectins are fucose-binding lectins with L-fucose (HX(26) RXDX(4)R/K) and calcium-binding sequence motifs and an F-type lectin fold (Bianchet et al 2002). They are phylogenetically widespread but selectively distributed in viruses, bacteria and eukaryotes (Bishnoi et al 2015), and have diverse functions ranging from innate immunity in fishes and amphibians to protoplast regeneration in the green alga, Bryopsis plumosa and virulence in the bacteria, Streptococcus pneumoniae and Streptococcus mitis (Vasta et al 2017). Several eukaryotic F-type lectins (e.g., Anguilla anguilla agglutinin (AAA), Morone saxatilis agglutinin (MSA)) (Bianchet et al 2002(Bianchet et al , 2010 and the F-type lectin domains (FLDs) of a couple of bacterial proteins (Streptococcus pneumoniae SP2159 and Streptococcus mitis lectinolysin) (Boraston et al 2006;Farrand et al 2008;Feil et al 2012) have been biochemically and structurally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The second domain of interest is CBM47, shown to be fucose-specific in the lectin regulatory domain of a cholesterol-dependent cytolysin present in some S. mitis strains (Feil, Lawrence et al 2012). It shares structure and sequence similarity with the F-lectins from fishes (Vasta et al, 2017). In our study, this fucose-binding module is identified in S. mitis as well as in some pathobionts, i.e.…”
Section: Predictions Of Carbohydrate Binding Modules In Vaginal Micromentioning
confidence: 54%
“…In order to characterise conserved motifs in lectin sequences, a new classification that accounts for different levels of sequence similarity, was needed. We ruled out using taxonomy as a classification criterion since low sequence similarity exists in some lectin families across kingdoms, such as the F-type lectins that are conserved from bacteria to mammals ( 26 ). In contrast, folds are more conserved than sequences and offer a more relevant criterion for building a classification.…”
Section: Update Of the Unilectin Portal And New Classification Of Lecmentioning
confidence: 99%